2008
DOI: 10.1111/j.1600-0722.2007.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Khat induces G1‐phase arrest and increased expression of stress‐sensitive p53 and p16 proteins in normal human oral keratinocytes and fibroblasts

Abstract: Khat is a psychostimulant plant used by over 10 million people daily, mainly in eastern Africa and the Middle East. Previous studies have suggested an association between khat use and oral lesions such as hyperkeratosis and oral cancer. This study investigated the effects of an extract of khat on primary normal human oral keratinocytes (NOK) and normal human oral fibroblasts (NOF). Low (sublethal) concentrations of khat inhibited the proliferation of both cell types in a dose-dependent and time-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…Based on cathinone, cathine and norephedrine concentrations in the khat-extract, the experimental dilutions should be comparative to local concentrations of khat constituents in vivo during khat chewing (Table 1) [26]. The impact on signal transduction proteins and stress sensors in T-lymphocytes, B-lymphocytes, natural killer (NK) cells and monocytes was assessed using modification-specific antibodies and flow cytometric analyses (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on cathinone, cathine and norephedrine concentrations in the khat-extract, the experimental dilutions should be comparative to local concentrations of khat constituents in vivo during khat chewing (Table 1) [26]. The impact on signal transduction proteins and stress sensors in T-lymphocytes, B-lymphocytes, natural killer (NK) cells and monocytes was assessed using modification-specific antibodies and flow cytometric analyses (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Our studies have shown that exposure of various cell types (i.e. leukemic cell lines, normal oral keratinocytes and fibroblasts, normal peripheral leukocytes) to khat-extract in vitro affects various proteins involved in cell death, cell stress, cell cycle regulation, differentiation and cell signaling [26,30,31,33,37]. …”
Section: Discussionmentioning
confidence: 99%
“…31 An organic Qat extract was shown to induce tumor suppressor proteins and G1 cell cycle arrest in normal oral fibroblast and keratinocytes in vitro. 32 Furthermore, the study showed that Qat induced premature differentiation and keratinization in oral keratinocytes grown in co-cultures with normal fibroblasts, possibly through signaling of p38 MAP kinase. 32 When exposed to a higher concentration of Qat the oral fibroblasts and keratinocytes underwent programmed cell death in a process involving reactive oxygen species.…”
Section: Qat Use and Effects On Healthmentioning
confidence: 97%
“…32 Furthermore, the study showed that Qat induced premature differentiation and keratinization in oral keratinocytes grown in co-cultures with normal fibroblasts, possibly through signaling of p38 MAP kinase. 32 When exposed to a higher concentration of Qat the oral fibroblasts and keratinocytes underwent programmed cell death in a process involving reactive oxygen species. 33 Moreover, the study also found that oxidative stress can occur in oral cells exposed to Qat.…”
Section: Qat Use and Effects On Healthmentioning
confidence: 97%
“…47,48 A more recent paper investigated the effects of qat on human oral keratinocytes and human oral fi broblasts in respect to changes present at the cell cycle level. 49 The results showed qat to have a strong inhibitory effect on the growth of these two cell types, with increased expression of tumour suppressor genes involving senescence related to differentiation. Whether these changes are mirrored in vivo is yet to be determined.…”
Section: Molecular-based Studies On Qatmentioning
confidence: 98%